Operating urban public transport rail infrastructure and vehicles over planned life cycle and its economic aspects within the company: (Analysis and fine-tuning of the science based continued operation protocol (scop) decision support model) - Takács, Péter (Studia Mundi – Economica, 2020)
If you accept the principle that a tangible asset can be operated as long as it is considered usable, operating conditions must be evaluated at the end of its life expectancy. Of course, life expectancy is different when we run a light bulb or an airplane therefore we will need some risk assessment and a science based continued operation protocol (SCOP). The idea of developing a SCOP came from BKV Zrt. and it was formed by 2012, with expertise help. SCOP is a model that keeps growing and requires fine tuning but the fact that BKV Zrt applies it on a daily basis, proves its success. In my thesis I now describe the key aspects of the operation of vehicles over the planned lifespan and analyse the model for further development.